Six‐arm Stellat Dendritic‐PbS Flexible Infrared Photodetector for Intelligent Healthcare Monitoring. Issue 8 (25th March 2022) - Zhang, Tuo; Ling, Cuicui; Wang, Xiaomeng; Feng, Bingxin; Cao, Min; Xue, Xin; Xue, Qingzhong; Zhang, Jianqiang; Zhu, Lei; Wang, Chuanke; Lu, Haipeng; Liu, Wenpeng
Abstract: The flexible photodetector plays an important role in improving human medical health status. However, the narrow spectral detection range, poor stress stability, and non‐degradation of traditional flexible photodetectors greatly hinder the further development of wearable medical devices. In this paper, a novel flexible infrared photodetector is proposed for intelligent healthcare monitoring using high purity lead sulfide (PbS) nanoparticles on paper‐based flexible substrate synthesized by hydrothermal method and physical friction. The excellent performance of the detector is attributed to the 1.01 eV band gap and six‐arm stellate dendritic structure of PdS, a good combination between PbS and paper substrate via physical friction. As a result, our photodetector demonstrates wide‐spectrum detection capabilities from 365 to 1550 nm. The photodetector at 980 nm (50.4 μW cm −2 ) shows responsivity of 6.45 mA W −1, detectivity of 6.4 × 10 10 Jones, response recovery time of 0.36 s/0.41 s, with good mechanical stability. By comparison, our detector has a wider detection range, better weak signal detection performance, and shorter response time than the performance of the former paper‐based detector. Furthermore, the paper‐based PbS photodetector as a dual‐wavelength photoplethysmography sensor is applied to analyze the oxygen saturation and develop an intelligent bandage to monitor wound healing. This paper‐based PbS photodetector has tremendous potential in the field of wearable medical devices and intelligent medical applications are expected. Abstract : A flexible, broadband, and biodegradable paper‐based six‐arm stellate dendritic (SASD) PbS infrared photodetector is developed. The excellent performance is attributed to the SASD structure of PdS and good combination between PbS and paper substrate via physical friction. Simultaneously, this photodetector is applied to measure the oxygen saturation and monitor the wound healing.